Idades de corte do capim-elefante BRS Canará para produção de forragem e feno - Ferreira, Eduardo André (2015)
The breakthrough in elephant grass cutting age implies increasing the amount of forage accumulated, however drastically reduces the quality of it. In this sense, should be established through the cut time an efficient management, enabling the balance of these factors. The objective of the study was to determine the age of the elephant grass cutting BRS Canará more suitable for production of chopped hay and forage in the dry season and water. The experiment was conducted at the Experimental Farm of the Federal University of Mato Grosso, located in Santo Antônio de Leverger, MT. The experimental design was a randomized block design with five treatments (cutting ages) and four replications each. Evaluated cutting ages were: 42, 56, 70, 84 and 98 days in the dry and 42, 60, 76, 91 and 105 days in water and hay production. Agronomic, morphological and chemical composition of chopped hay and elephant grass pasture were evaluated. During the dry season, with the advance in age there was an increase of the width of the last fully expanded leaf blade, forage yield, pseudoculm percentages and senescent material, reducing the percentage of leaf blades and leaf blade: pseudoculm. In the same period, there was an increase in DM, ADF, and NDFi NDFap, indigestible protein and neutral detergent acid and reduced levels of ash, CP, NDT and net energy of lactation. In the rainy season, with the advance in age, there was an increase in plant height, stem diameter, forage yield, percentage of stems and reduce the percentage of leaf blades. In the same period, there was an increase in DM, ADF, NDFi, NDFap, indigestible protein and neutral detergent to reduce the yields of ash, CP, NDT and net energy of lactation. For the chopped hay, as increasing age, there was an increase of hay yield and DM, FDA, NDFi, NDFap, indigestible protein and neutral detergent to reduce the yields of ash, CP, NDT and net energy of lactation. The cut elephant grass BRS Canará for production of chopped hay and forage production during the wet season should be performed between 60 and 76 days and for forage production during the dry season should be performed between 56 and 70 days.